2004
DOI: 10.1111/j.1365-2141.2004.05274.x
|View full text |Cite
|
Sign up to set email alerts
|

Advanced glycation end‐products in sickle cell anaemia

Abstract: Summary Tissue accumulation of advanced glycation end‐products (AGEs) has been implicated in the oxidant‐induced vascular pathology of diabetes and other diseases. Because homozygous sickle cell anaemia (SCA) is a state of oxidative stress, we tested the hypothesis that circulating AGE levels are elevated in SCA. Blood was obtained from age‐ and race‐matched children classified as either non‐sickle cell controls, SCA without vaso‐occlusive crisis (SCA − VOC), or SCA with vaso‐occlusive crisis (SCA + VOC). Plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 32 publications
4
33
0
Order By: Relevance
“…A PubMed search shows that in the 1980s, 1990s, and 2000s, the number of articles on AGEs was 21, 978, and >3700, respectively. Epidemiological studies have suggested that individuals with higher elevated circulating CML, are at greater risk of arterial stiffness, (12) chronic kidney disease, (13) anemia, (14) cardiovascular and all-cause mortality. (15) The data provided here support the use of stored samples, regardless of collection and storage method, from other epidemiological studies for the analysis of CML and CEL to further examine the association between AGEs and disease risk.…”
Section: Discussionmentioning
confidence: 99%
“…A PubMed search shows that in the 1980s, 1990s, and 2000s, the number of articles on AGEs was 21, 978, and >3700, respectively. Epidemiological studies have suggested that individuals with higher elevated circulating CML, are at greater risk of arterial stiffness, (12) chronic kidney disease, (13) anemia, (14) cardiovascular and all-cause mortality. (15) The data provided here support the use of stored samples, regardless of collection and storage method, from other epidemiological studies for the analysis of CML and CEL to further examine the association between AGEs and disease risk.…”
Section: Discussionmentioning
confidence: 99%
“…Gastrointestinal/Hepatologic: autoimmune hepatitis [38], chronic constipation [112], inflammatory bowel disease [47], nonalcoholic fatty liver disease [75,106], viral hepatitis [19], Wilson disease [78] Genetic: Cockayne syndrome [49], Down syndrome [54,57], Zellweger syndrome [44] Hematologic: acute leukemia [52,53,88], β-thalassemia [45], erythropoietic protoporphyria [104], Fanconi anemia [72], sickle cell anemia [93] Infectious: acute bronchiolitis [70], acute infectious mononucleosis [48], acute otitis media [102], acute tonsillitis [102], adenovirus infection [48], chronic nail candidiasis [80], chronic otitis media [87], chronic tonsillitis [62,82] [90], inflammatory myopathy [60], selenium-deficient skeletal muscle disorder [59], spinal muscular atrophy [24], traumatic brain injury [36,46] Investigation of the role of oxidative stress in pediatric diseases requires information about the oxidative stress status of young populations. It will be possible to evaluate the contribution of oxidative stress to various pediatric diseases and establish better approaches for each disease when we know normal levels of oxidative stress in children and adolescents.…”
Section: Possible Oxidative Stress Involvement In Pediatric Diseasementioning
confidence: 99%
“…[3][4][5] RBC and other cell types show evidence of lipid peroxidation and oxidative damage to structural proteins. [6][7][8] Additionally, plasma from SCD patients has elevated levels of advanced glycation end products 9,10 and products of lipid peroxidation (F-2 isoprostanes, malonaldehyde, and 4-hydroxynonenal), [11][12][13] all of which are markers of oxidative stress. There are several postulated mechanisms for the increased oxidative stress in patients with SCD.…”
Section: Introductionmentioning
confidence: 99%